An Integrated Systems Engineering Method for Conceptual Design of Vehicle Handling Dynamics. Issue 6 (November 2015) - Hazare, Mandar; Venhovens, Paul
ABSTRACT: The handling characteristics of road vehicles are important attributes that define a major part of its unique selling proposition. The engineering process of tuning vehicle handling dynamics is a challenging process due to the multitude of competing design requirements/parameters and requires a well‐defined systematic approach. The primary objective of this publication is to describe an integrated system engineering method for the conceptual design of vehicle handling dynamics early in the product development process. A systems engineering‐based simulation framework is described that connects subjective, customer‐relevant handling expectations to higher‐level, objective vehicle engineering targets and consequently breaks these targets down into subsystem‐level requirements and component‐level design specifications. A case study supporting this proposed system engineering method for vehicle handling design is also described in detail. The integrated systems engineering approach guides the engineering development process and provides insight into the compromises involved in vehicle handling layout, ultimately saving product development time and costs and helping to achieve a higher level of product maturity early in the design phase.